Current problems of the influence of international legislation statutes on the institution of citizenship in foreign countries - Balgimbekova, G.U.; Rysmendeyev, B.D.; Botagarin, R.B. (Bulletin of the Karaganda University “Law Series”, 2021)
This article analyzes the international human rights legislation that regulates the right to citizenship and has influenced this institution in several foreign countries. The citizenship as a constitutional and legal institution is a set of norms of national and international law that sets up the conditions and procedures for establishing, changing, terminating and realizing the subjective rights of people with disabilities to citizenship. Further consistent and purposeful development of constitutional and legal norms guaranteeing human rights and freedoms by further strengthening the institution of citizenship is one of the most important tasks of constitutional law. Determining the nature of citizenship as a political and legal phenomenon, as well as political and legal relations between a person and a state, is problematic, but there is no clear answer in the legal doctrine given that such a stratified phenomenon can be viewed from different angles taking into account different methods and ideological approaches. Based on the study and analysis of foreign legislation in the field of application of international legal acts regulating the issue of citizenship, it is possible to develop methods for the development of this system. When studying the problem by the method of comparative jurisprudence, an analysis of the existing legal framework in the Republic of Kazakhstan and foreign countries was carried out and international legal acts in the field of regulation of citizenship issues were studied. The purpose of the article is to understand the importance of the role of international law in influencing the status of people (citizenship) in modern states and societies.